Utilisation and Tolerability of Aliskiren in the Primary Care Setting in England. Issue 12 (3rd June 2016) - Coughtrie, Abigail L.; Doe, Claire; Layton, Deborah; Shakir, Saad A. W.
Abstract : Aliskiren (Rasilez), a direct renin inhibitor, is indicated for the treatment of essential hypertension. A postmarketing prescription‐event monitoring (PEM) study was conducted in England to monitor the safety and utilization of aliskiren. Summary statistics and event incidence densities were calculated. The cohort consisted of 6385 individuals with a median age of 68 years (interquartile range, 59–76). Aliskiren was largely prescribed for its licensed indication of hypertension (93.3%) and was reported as "effective" by the prescriber in 77.4% of individuals. Frequently reported clinical events during treatment were diarrhea (3.1% of on‐treatment events), malaise/lassitude (3.0%), and nausea/vomiting (1.2%), which were also common reasons for treatment cessation. Renal events were rare, with 24 cases probably or possibly related to aliskiren use, and four of which were classified as acute renal failure using RIFLE (Risk Injury Failure Loss End‐Stage Kidney Disease) criteria. These results should be used in conjunction with other clinical and pharmacoepidemiologic studies to optimize the safe prescribing of aliskiren.